Perceiving Ourselves and Others: Neural Signatures of Cognitive, Social, and Affective Processes Related to the Perception of Ourselves, Our Body, and the Social World - Michael Schaefer (Brain Sciences, 2022)
An essential task of any system is to distinguish between itself and its environment, between what is inside and that which is outside [...]